The Impact of Report writing Training on the Quality of Auditory Reporting in Audiology Students and Graduates of Ahvaz University of Medical Sciences in 1396-1398 - maryam Delfi; Marzieh Amiri; Arash Bayat; Mojtaba Tavakoli; Fatemeh Taheri; Sahar Shamil Shoshtari (Babol University of Medical Sciences, 2020)
ABSTRACT BACKGROUND AND OBJECTIVE: Report writing is a necessary framework for presentation of audio logical test results. One of the methods of teaching report writing is workshops. The overall purpose of this study was to investigate the impact of report writing on the quality of audiology reporting in Ahvaz University of Medical Sciences. METHODS: This study is a quasi-experimental (before and after). 57 audiologists participated in the report writing workshop and completed pre- and post-test questions. A checklist was used to collect the data. Data were analyzed using SPSS 21 software. Descriptive statistics were used to describe the data and Wilcoxon statistical test was used to compare the results before and after the intervention. FINDINGS: The findings of this study showed following  report writing training, the mean scores before and after the training showed a significant difference (P<0.001). And in all items improves the quality of reporting in audiology tests. CONCLUSION: Based on this findings, report writing training improves the quality of reporting in audiologists, and given that there isn't formal training in this field, it is recommended to provide a workshop for all students in audiology.